R-Loops in proliferating cells but not in the brain : implications for AOA2 and other autosomal recessive ataxias - Yeo, Abrey J. (2014)
Disruption of the Setx gene, defective in ataxia oculomotor apraxia type 2 (AOA2) leads to the accumulation of DNA/RNA hybrids (R-loops), failure of meiotic recombination and infertility in mice. We report here the presence of R-loops in the testes from other autosomal recessive ataxia mouse models, which correlate with fertility in these disorders. R-loops were coincident in cells showing high basal levels of DNA double strand breaks and in those cells undergoing apoptosis. Depletion of Setx led to high basal levels of R-loops and these were enhanced further by DNA damage both in vitro and in vivo in tissues with proliferating cells. There was no evidence for accumulation of R-loops in the brains of mice where Setx, Atm, Tdp1 or Aptx genes were disrupted. These data provide further evidence for genome destabilization as a consequence of disrupted transcription in the presence of DNA double strand breaks arising during DNA replication or recombination. They also suggest that R-loop accumulation does not contribute to the neurodegenerative phenotype in these autosomal recessive ataxias.